The Impact of Management Information Systems on Decision-Making Quality in Emerging Companies - Taher Ali Taher Brideh; Amer Salem Ali Salem (African Journal of Advanced Pure and Applied Sciences, 2025)
Management Information Systems (MIS) combine people, processes, data and technology to provide timely, relevant information for organizational decision-making. This paper examines how MIS deployment can improve decision-making quality in emerging companies, which often lack mature information processes. Emerging firms frequently handle data in basic ways and have limited information access. We review literature on MIS functions and decision processes, and present examples showing MIS benefits. A case study of a small enterprise reported that implementing an MIS reduced report generation time by 21.2% and eliminated manual errors. High-quality, timely information from MIS is shown to improve decision speed and accuracy. The paper includes data-driven diagrams and charts, and discusses practical experiences from industry. Our findings suggest that even in resource-constrained emerging companies, MIS can significantly enhance the efficiency and quality of managerial decisions.